Finite element method model to predict bulk and flash temperatures on polymer gears - Carlos M. C. G. Fernandes (2018)
A FEM thermal model was implemented to predict the bulk and flash temperature of gears in general and polymer gears in particular. Using the capabilities of a gear power loss model previously validated, a solution for the temperature rise and distribution along the tooth is suggested. The accuracy of the power loss model is decisive for the prediction of gear temperature field by FEM model. The FEM model was validated with experimental results from the literature. The model allows to predict the bulk temperatures for oil jet, dip lubrication or non-lubricated conditions. The FEM model allows an higher accuracy on the calculation of the load carrying capacity of polymer gears, whose mechanical properties are critically dependent on the bulk temperature.